Upaya meningkatkan hasil belajar kognitif tema benda, hewan dan tanaman di sekitarku menggunakan model pembelajaran take and give berbantuan media flashcard bagi siswa kelas I SD Negeri Maguan - Suwanti Suwanti (Jurnal Pendidikan Dasar, 2020)
Abstract. the purpose of this research is to understand whether the using of take and give learning model assisted with flashcard media improve the First Class students of Maguan Elementary School, Sub district of Kaliori, Regency of Rembang on the Second Semester of the 2018/2019 Year Academic the cognitive learning result on thematic learning. The subjects of this research are 14 students consist of 7 boys and 7 girls. Independent variable is the take and give learning model assisted with flashcard. Dependent variable is the cognitive learning result on thematic learning. Techniques of collecting data are test and observation. The instruments of collecting data are the test result and sheet of observation. The data analyzing showed the improving of the cognitive learning result on thematic learning. From the Early Condition to the First Cycle and Second Cycle, the learning results improve. The completenesson the Early Condition is 8 students or 57%, after the learning on the First Cycle thecompleteness improve as 11 students or 79%, on the Second Cycle the completeness improve 13 students or 93%. Meanwhile the averages also improve. On the Early Condition, the average is 73,79, improve up to 83 after the action on the First Cycle, then on the Second Cycle improve up to 90,71Keywords: Learning Outcomes, Take and Give, Flashcard Media.